Discursive Toxicity and Cyberbullying in TikTok User Comments: A Critical Discourse Analysis Approach - Dio Manik; Yeni Adventry Tanjung; Annisa Ananda Utomo; Amelia Amelia; Muhammad Natsir (Student Scientific Creativity Journal, 2026)
The rapid development of social media has created new spaces of interaction that not only expand public participation but also give rise to problematic communication practices, such as toxicity and cyberbullying in netizen comments. This phenomenon has become increasingly relevant in the context of contemporary digital society, where the boundary between individual expression and verbal aggression is often blurred. This study aims to understand how discursive practices in netizen comments shape, reproduce, and construct the meaning of toxicity and cyberbullying from the participants’ perspectives. Employing a qualitative approach with a case study design, the research involves 10–15 participants who are active social media users in Indonesia. Data were collected through in-depth interviews, non-participant observation, and document analysis of digital comments, and were analyzed using thematic analysis combined with a Critical Discourse Analysis (CDA) framework. The findings reveal three primary patterns: the normalization of verbal aggression as part of digital communication culture, psychological distress that leads to ambivalent coping strategies, and the dynamics of social identity that reinforce polarization in online interactions. These findings suggest that cyberbullying is not merely an individual act but a discursive practice embedded in power relations and digital social norms. Theoretically, this study enriches discourse analysis by integrating linguistic, social, and subjective experiential dimensions; practically, it offers implications for strengthening digital literacy, content moderation policies, and mental health based interventions. Furthermore, this research opens avenues for broader and more diverse explorations of digital discourse dynamics.